Targeting indoor residual spraying for malaria using epidemiological data: a case study of the Zambia experience. (December 2016) - Pinchoff, Jessie; Larsen, David; Renn, Silvia; Pollard, Derek; Fornadel, Christen; Maire, Mark; Sikaala, Chadwick; Sinyangwe, Chomba; Winters, Benjamin; Bridges, Daniel; Winters, Anna
Abstract Background In Zambia and other sub-Saharan African countries affected by ongoing malaria transmission, indoor residual spraying (IRS) for malaria prevention has typically been implemented over large areas, e.g., district-wide, and targeted to peri-urban areas. However, there is a recent shift in some countries, including Zambia, towards the adoption of a more strategic and targeted IRS approach, in coordination with increased emphasis on universal coverage of long-lasting insecticidal nets (LLINs) and effective insecticide resistance management. A true targeted approach would deliver IRS to sub-district areas identified as high-risk, with the goal of maximizing the prevention of malaria cases and deaths. Results Together with the Government of the Republic of Zambia, a new methodology was developed applying geographic information systems and satellite imagery to support a targeted IRS campaign during the 2014 spray season using health management information system data. Discussion/Conclusion This case study focuses on the developed methodology while also highlighting the significant research gaps which must be filled to guide countries on the most effective strategy for IRS targeting in the context of universal LLIN coverage and evolving insecticide resistance.